Time-averaged flow over a hydrofoil at high Reynolds number - BOURGOYNE, DWAYNE A.; HAMEL, JOSHUA M.; CECCIO, STEVEN L.; DOWLING, DAVID R. (Journal of fluid mechanics, 2003)
At high Reynolds number, the flow of an incompressible viscous fluid over a lifting surface is a rich blend of fluid dynamic phenomena. Here, boundary layers formed at the leading edge develop over both the suction and pressure sides of the lifting surface, transition to turbulence, separate near the foil's trailing edge, combine in the near wake, and eventually form a turbulent far-field wake. The individual elements of this process have been the subject of much prior work. However, controlled experimental investigations of these flow phenomena and their interaction on a lifting surface at Reynolds numbers typical of heavy-lift aircraft wings or full-size ship propellers (chord-based Reynolds numbers, $Re_C {\sim} 10^7{-}10^8$) are largely unavilable. This paper presents results from an experimental effort to identify and measure the dominant features of the flow over a two-dimensional hydrofoil at nominal $Re_C$ values from near one million to more than 50 million. The experiments were conducted in the US Navy's William B. Morgan Large Cavitation Channel with a solid-bronze hydrofoil (2.1 m chord, 3.0 m span, 17 cm maximum thickness) at flow speeds from 0.25 to 18.3 m s$^{-1}$. The foil section, a modified NACA 16 with a pressure side that is nearly flat and a suction side that terminates in a blunt trailing-edge bevel, approximates the cross-section of a generic naval propeller blade. Time-averaged flow-field measurements drawn from laser-Doppler velocimetry, particle-imaging velocimetry, and static pressure taps were made for two trailing-edge bevel angles (44$ ^°$ and 56$ ^°$). These velocity and pressure measurements were concentrated in the trailing-edge and near-wake regions, but also include flow conditions upstream and far downstream of the foil, as well as static pressure distributions on the foil surface and test section walls. Observed Reynolds-number variations in the time-averaged flow over the foil are traced to changes in suction-side boundary-layer transition and separation. Observed Reynolds-number variations in the time-averaged near wake suggest significant changes occur in the dynamic flow in the range of $Re_C$ investigated.